Epidemiological and Clinical Profile of Rotavirus Gastroenteritis among Children Younger than 5 Years of Age (Indian Journal of Child Health, 2021)
Background: Acute gastroenteritis is on one of the leading causes of morbidity and mortality in children below 5 years of age. Among the various pathogens, rotavirus (RV) is responsible for 25–50% of all diarrheal hospitalizations. Objective: The objective of the study was to assess epidemiological and clinical features of RV among children younger than 5 years of age hospitalized with acute gastroenteritis and to compare it with RV negative diarrhea. Materials and Methods: A prospective descriptive hospital-based study was carried out among 162 children with acute gastroenteritis in a tertiary care teaching hospital from April 2017 to March 2018. Epidemiological profile, clinical features, and laboratory findings were recorded and compared between RV diarrhea (n=53) with non-RV (NRV) diarrhea (n=109) cases. Results: Mean age of patients was comparable between groups (RV-19.52±11.3 months; NRV-18.0±14 (p=0.47). Peak RV infection was observed during winters (66.03%) and NRV diarrhea occurred predominantly during summer months (38.53%). Comparison of clinical features of acute gastroenteritis between groups showed higher incidence of vomiting (p=0.006), diarrhea (p=0.049), and severity based on the Vesikari score (p=0.003) in RV group. Severe dehydration was observed in 5.6–7.3% in RV and NRV group, respectively (p=0.635). Around 26.41% incidence of dyselectrolytemia was seen in RV group. Conclusion: Studying the epidemiology and clinical profile of RV diarrhea will not only help in management of diarrhea, but will also provide useful information for indigenous vaccine development in India.